2019
DOI: 10.1037/pha0000261
|View full text |Cite
|
Sign up to set email alerts
|

Abuse liability assessment of an electronic cigarette in combustible cigarette smokers.

Abstract: Under certain conditions, electronic cigarettes (e-cigs) can deliver nicotine to and suppress tobacco abstinence symptoms in cigarette smokers. Growing popularity of e-cigs raises abuse liability concerns. This study's purpose was to compare the abuse liability of an e-cig (1.5 Ohm, 3.3 V) filled with 36 mg/mL or 0 mg/mL nicotine to an Food and Drug Administration (FDA)-approved nicotine inhaler (IN) and participants' own brand (OB) of cigarettes. Smokers (N ϭ 24) completed four sessions in which they complete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
27
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(33 citation statements)
references
References 63 publications
5
27
1
Order By: Relevance
“…The method for this VCU IRB-approved study was similar to that reported elsewhere 8 9. Briefly, community volunteers aged 18–55 who smoked > 10 cigarettes daily and with expired air carbon monoxide (CO) > 15 ppm at screening and who reported no JUUL or IQOS experience were recruited to complete three, ~4 hour, Latin-square ordered sessions that were each preceded by 12 hours of nicotine/tobacco abstinence (verified with CO < 10 ppm and baseline plasma nicotine concentration <5.0 ng/mL8 10). Sessions differed by product used: JUUL (tobacco or mint flavour pod), IQOS (tobacco or menthol) or OB cigarette (OB; JUUL and IQOS flavours were matched to OB).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The method for this VCU IRB-approved study was similar to that reported elsewhere 8 9. Briefly, community volunteers aged 18–55 who smoked > 10 cigarettes daily and with expired air carbon monoxide (CO) > 15 ppm at screening and who reported no JUUL or IQOS experience were recruited to complete three, ~4 hour, Latin-square ordered sessions that were each preceded by 12 hours of nicotine/tobacco abstinence (verified with CO < 10 ppm and baseline plasma nicotine concentration <5.0 ng/mL8 10). Sessions differed by product used: JUUL (tobacco or mint flavour pod), IQOS (tobacco or menthol) or OB cigarette (OB; JUUL and IQOS flavours were matched to OB).…”
Section: Methodsmentioning
confidence: 99%
“…Product use consisted of one 10-puff ‘directed’ bout (30 s interpuff interval) and, after 25 min rest, a 90 min ad libitum bout. Blood was sampled via a catheter placed in a forearm vein before and immediately after each bout, heart rate and blood pressure were monitored continuously (heart rate and blood pressure data not reported), and expired air CO (Vitalograph; Lenexa, Kansas, USA) and subjective effects10 were measured before and after each bout. Participants were compensated US$100 after each session.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A standard methodology has been established to assess the abuse liability of pharmaceuticals (285) and is largely adaptable for tobacco products (280,286). This type of study is likely to be most relevant in countries where high concentrations of nicotine are allowed in e-liquids, such as the USA (287).…”
Section: Switching To Ecs and Abuse Liabilitymentioning
confidence: 99%
“…Nevertheless, one study demonstrated that 54% of smokers incorrectly believed that reductions in nicotine made cigarettes less dangerous [7]. Additionally, young adults (a priority population for tobacco control) commonly have misperceptions about the safety profile and nicotine content in e-cigarettes [8], including the unsubstantiated belief that e-cigarettes are relatively safe despite the burgeoning evidence indicating the products' nicotine-related abuse potential [9,10] and associations with progression to regular combustible cigarette use [11].…”
Section: Introductionmentioning
confidence: 99%